2020
DOI: 10.1093/nutrit/nuaa113
|View full text |Cite|
|
Sign up to set email alerts
|

Ketogenic diet and cognition in neurological diseases: a systematic review

Abstract: Context In recent years, the ketogenic diet has gained special relevance as a possible therapeutic alternative to some neurological and chronic diseases. Objective The aim of this systematic review was to answer the following question: Does a ketogenic diet improve cognitive skills in patients with Alzheimer's disease, Parkinson's disease, refractory epilepsy, and type 1 glucose deficiency syndrome? To define the research que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 54 publications
0
14
0
2
Order By: Relevance
“…For example, an increasing number of preclinical studies suggest the KD as a potent anticancer therapy because of its direct effects on tumor growth, which may improve the overall health status of patients as well as their QOL [51,52]. In patients with neurological disorders such as Alzheimer's disease, although the literature is scarce and lacks scientific rigor, KD seems to improve the cognitive symptomatology of these diseases, hence its speculated effect on QOL in this patient population [53]. The possible neuroprotective effects of the KD could potentially reside in its beneficial effect on reducing accumulation of amyloid plaques, protecting against amyloid-beta toxicity, and through the modification of the neuronal network activity, although precise mechanisms remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…For example, an increasing number of preclinical studies suggest the KD as a potent anticancer therapy because of its direct effects on tumor growth, which may improve the overall health status of patients as well as their QOL [51,52]. In patients with neurological disorders such as Alzheimer's disease, although the literature is scarce and lacks scientific rigor, KD seems to improve the cognitive symptomatology of these diseases, hence its speculated effect on QOL in this patient population [53]. The possible neuroprotective effects of the KD could potentially reside in its beneficial effect on reducing accumulation of amyloid plaques, protecting against amyloid-beta toxicity, and through the modification of the neuronal network activity, although precise mechanisms remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Diet is a rapid and direct way of modifying the gut microbiota composition and function, reducing inflammation, and helping in eubiosis maintenance [ 123 , 164 , 165 ]. Given the evidence of association between neuropsychiatric conditions and gut microbiota dysregulation, it is worth speculating that dietary interventions could represent effective candidates for preventing and delaying the pathogenesis and progression of AD [ 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 ] ( Table 2 ). Here, we present some of the most promising dietary therapies proposed in the literature, with a particular focus on Mediterranean and ketogenic diets.…”
Section: Mainmentioning
confidence: 99%
“…In humans, results from RCT reported that KD might be beneficial in people with mild cognitive impairment or AD [ 171 , 172 ]. Similar to KD in terms of mechanisms (i.e., ketone bodies production), medium-chain triglyceride (MCT) diet/supplementation and the modified Atkins diet are effective in counteracting cognitive decline in AD, symptoms such as fatigue and daytime sleepiness in PD, epileptic seizures and mood swings in depression [ 173 , 174 , 175 , 217 , 218 ]. Moreover, the modified Atkins diet, which does not restrict protein intake as the KD protocol, allows a much more nutritional flexibility than classic KD.…”
Section: Mainmentioning
confidence: 99%
“…Alzheimer hastalığının gelişmesine ve ilerlemesine neden olduğu kabul edilen nöroprotektif mekanizmalardan birisi β-Amiloid plak birikimidir. Fare modelli yapılan çalışmalarda ketojenik diyetin β-Amiloid seviyelerini düşürdüğü ve nöronlara girişinin engelleyerek hücre içi agregasyonunu azalttığı gözlemlenmiştir 17,2 . Kashiwaya ve ark., ketojenik diyetin β-Amiloid ve tau proteini üzerine etkisini inceledikleri çalışmada, transgenik 30 fareyi iki gruba ayırarak, 15 ay boyunca keton esteri içeren bir diyet veya karbonhidratla zenginleştirilmiş bir diyet vermişlerdir.…”
Section: Tau Proteinine Ve β-Amiloid Plak Oluşumuna Etkisiunclassified
“…Alzheimer, beynin çeşitli bölgelerinde gerçekleşen nöron dejenerasyonlarını takiben beyin fonksiyonlarında azalma görülen bir hastalıktır. Hastalığın evrimi hem progresif hem de geri dönüşsüz olup özellikle hafıza kaybı ile ortaya çıkar 1,2 . Dünyada artan yaşlı popülasyonuyla birlikte daha sık karşılaşılan Alzheimer hastalığının patogenezini açıklamaya ilişkin birçok hipotez geliştirilmiştir.…”
Section: Introductionunclassified